STUDYING THE EFFECT OF MICRO BUBBLES IN REMOVING THE SUSPENDED PARTICLES IN CMC POLLUTED WATER - Winarto, F Eko Wismo (2009)
ABSTRACT Waste water is polluted water. The water can be purified first by identifying the types of pollutant. There are two types of physical water pollutant, which are suspended particles and colloids. Both can be expressed by the measure of turbidity level. Measuring the polluted number, PPM (part per millions) is a complicated step. Micro bubble technique was used for removal of the suspended particles.